Overview of Filipino Veterans' Benefits. (U.S. Congressional Research., 2009)
Provides overview of major Filipino veterans legislation enacted by Congress from 1946 through 2003. Defines specific groups of Filipino nationals who served under U.S. command, and outlines the Rescission Acts of 1946, benefit expansions from 1948 onward, and recent related legislative proposals.